2014
DOI: 10.1063/1.4900437
|View full text |Cite
|
Sign up to set email alerts
|

Control of domain wall pinning by localised focused Ga + ion irradiation on Au capped NiFe nanowires

Abstract: Understanding domain wall pinning and propagation in nanowires are important for future spintronics and nanoparticle manipulation technologies. Here, the effects of microscopic local modification of the magnetic properties, induced by focused-ion-beam intermixing, in NiFe/Au bilayer nanowires on the pinning behavior of domain walls was investigated. The effects of irradiation dose and the length of the irradiated features were investigated experimentally. The results are considered in the context of detailed q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The shaded region indicates the dose region where α is expected to be maximum according to the trend of experimental data points. Structurally, ion beam irradiation leads predominantly to ballistic intermixing and some insight into the evolution of the NiFe/Pt interface may be gained from previous detailed x-ray structural analysis of FIB irradiated NiFe/Au bilayers 24 25 40 42 since the process is dominated by momentum transfer and the atomic mass of Pt is close to that of Au. The interface in as-deposited NiFe/Au and NiFe/Pt has some small intrinsic width (~1 nm from XRR measurements) and with increasing irradiation dose the interface width increases linearly due to intermixing of the layers, creating an increasing thickness of compositionally-graded NiFePt alloy between the NiFe and Pt.…”
Section: Resultsmentioning
confidence: 99%
“…The shaded region indicates the dose region where α is expected to be maximum according to the trend of experimental data points. Structurally, ion beam irradiation leads predominantly to ballistic intermixing and some insight into the evolution of the NiFe/Pt interface may be gained from previous detailed x-ray structural analysis of FIB irradiated NiFe/Au bilayers 24 25 40 42 since the process is dominated by momentum transfer and the atomic mass of Pt is close to that of Au. The interface in as-deposited NiFe/Au and NiFe/Pt has some small intrinsic width (~1 nm from XRR measurements) and with increasing irradiation dose the interface width increases linearly due to intermixing of the layers, creating an increasing thickness of compositionally-graded NiFePt alloy between the NiFe and Pt.…”
Section: Resultsmentioning
confidence: 99%
“…The use of constrictions 19 20 21 , notches 22 23 24 25 and regions of reduced M S 26 have previously been explored as mechanisms to controllably pin a DW at a known position within a nanowire structure. These ideas are based upon local modifications of the energy landscape of the wire to present a potential well or barrier to a DW.…”
mentioning
confidence: 99%
“…Thus, this is a potential technique for creating the pinning sites for the DW memory devices. Burn et al in 2014 reported Ga + ion irradiation on Permalloy nanowires as technique for creating the pinning sites [61]. They reported a decrease in magnetization upon the Ga + ion irradiation.…”
Section: B Ion Implantationmentioning
confidence: 99%